Etnografía feminista en contextos de múltiples violencias; Feminist ethnography in contexts of multiple violences - Hernández Castillo, Rosalba Aída (Universidad Autónoma Metropolitana)
In this article I will address the implications of making a feminist ethnography from collaborative methodologies. These collaborative methodologies recognize the privilege, but also the vulnerabilities, that we have as anthropologist-activists in social contexts marked by patriarchal violence. Taking as case studies three activist-research experiences with indigenous women victims of sexual violence, women in prison, and relatives of the disappeared persons, I reflect on the methodological strategies that can be used to make a feminist ethnography from an ethic of care and a decolonial perspective.; En este artículo se abordarán las implicaciones de hacer una etnografía feminista desde metodologías colaborativas, que reconocen los privilegios, pero también las vulnerabilidades que tienen las antropólogas-activistas, en contextos sociales marcados por las violencias patriarcales. Tomando como estudios de caso tres experiencias de investigación activista –con mujeres indígenas víctimas de violencia sexual, con mujeres en reclusión y con familiares de personas desaparecidas– se reflexiona sobre las estrategias metodológicas que pueden servir para hacer una etnografía feminista, desde una ética del cuidado y una perspectiva descolonial.